Pengaruh Harga Dan Lokasi Terhadap Kepuasan Pelanggan Pada X-Mart - Praga, Jaya; Handoko , Dedi; Nurlaila, Dila (Journal of Applied Accounting And Business, 2026)
This study aims to analyze the effect of price and location on customer satisfaction at Poljam Mart Permataland. Increasing competition in the retail business requires companies to understand the factors that influence customer satisfaction in order to maintain customers and improve business performance. This research uses a quantitative method with descriptive and verificative approaches. Research data were collected through questionnaires distributed to 75 respondents who are customers of Poljam Mart Permataland using an accidental sampling technique. The research instrument used a Likert scale and the data were analyzed using multiple linear regression analysis with statistical software. The results show that price has a positive and significant effect on customer satisfaction, location has a positive and significant effect on customer satisfaction, and price and location simultaneously have a positive and significant effect on customer satisfaction at Poljam Mart Permataland. The conclusion indicates that appropriate pricing and a strategic location play an important role in increasing customer satisfaction.